Intravascular Clearance of Parasitized Erythrocytes in Rodent Malaria - Quinn, Thomas C. (1979)
Little is known about host defense mechanisms responsible for protective immunity in malaria. The intravascular location of the infection suggested that removal of parasitized erythrocytes by reticuloendothelial organs might be important. To study this possibility, we examined the clearance of (51)Crlabeled Plasmodium berghei-infected erythrocytes in rats. Infected erythrocytes were removed more rapidly from circulation than homologous uninfected erythrocytes. The rate of clearance of infected cells during the 1st hour after inoculation was approximately three times greater in rats rendered immune by prior infection than in control rats. This accelerated clearance resulted from greater splenic uptake in immune rats and appeared to correlate with spleen size. Since the clearance pattern of infected erythrocytes more closely resembled the clearance of Heinz body-containing uninfected erythrocytes than of antibody-coated (immunoglobulin G) uninfected erythrocytes, rheologic alterations of parasitized erythrocytes might be a more important determinant of clearance than an antibody-dependent process. During the phase of malaria infection in which increasing parasitemia is observed, organ uptake of infected erythrocytes did not increase despite splenic and hepatic enlargement. However during the spontaneous onset of resolution of malaria infection characterized by decreasing parasitemia, a marked enhancement of splenic clearance was noted. These observations suggest that sudden alteration in splenic clearance of parasitized erythrocytes might be important in the resolution of acute malaria.